2022
DOI: 10.3389/fphar.2021.809595
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Clostridioides difficile Toxins TcdA and TcdB by Ambroxol

Abstract: Clostridioides (C.) difficile produces the exotoxins TcdA and TcdB, which are the predominant virulence factors causing C. difficile associated disease (CDAD). TcdA and TcdB bind to target cells and are internalized via receptor-mediated endocytosis. Translocation of the toxins’ enzyme subunits from early endosomes into the cytosol depends on acidification of endosomal vesicles, which is a prerequisite for the formation of transmembrane channels. The enzyme subunits of the toxins translocate into the cytosol v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Castanospermine, a compound described as a potent inhibitor of the GTD of TcdB, was used as positive control in this assay. 14 , 24 Whereas 10 mM castanospermine showed, as expected, robust inhibition of the glucosyltransferase activity of TcdB (~50% reduction), the same approach with 30 and 100 µM amiodarone yielded no inhibition ( Figure 6b ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Castanospermine, a compound described as a potent inhibitor of the GTD of TcdB, was used as positive control in this assay. 14 , 24 Whereas 10 mM castanospermine showed, as expected, robust inhibition of the glucosyltransferase activity of TcdB (~50% reduction), the same approach with 30 and 100 µM amiodarone yielded no inhibition ( Figure 6b ).…”
Section: Resultssupporting
confidence: 66%
“…The reaction was performed with UDP-glucose as co-substrate and with the GTPase Rac1 as substrate, which was recombinantly purified from Escherichia coli as described previously. 24 In brief, all reactions were performed for 1 h at 37°C in a total volume of 15 µl of glucosylation buffer (50 mM HEPES, 100 mM KCl, 2 mM MgCl 2 , 1 mM MnCl 2 , 100 mg/L BSA, pH 7.5), including 200 pM TcdB, 100 µM UDP-glucose, 5 µM Rac1, and, optionally, amiodarone (30 or 300 µM) or castanospermine (10 mM). Next, 10 µl of each reaction was transferred to a 96-well half-area microplate (Greiner, #675075, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Native TcdB from C. difficile VPI 10,463 was expressed and purified as described earlier [ 48 ]. Rac1 was expressed and purified as a recombinant GST-tagged protein as described previously [ 49 ]. Native TcdA was obtained from List (Campbell, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A newer option is blocking the toxins. Calcium aluminosilicate and human serum albumin have shown toxin-binding activity in vitro; some researchers report that aspirin has a good effect, and recent data has shown that human alpha-defensins and ambroxol have antitoxic activity [112,113]. The information for the important treatment options is shown in Table 1.…”
Section: Treatmentmentioning
confidence: 99%